Pemeriksaan Kesehatan Gratis Menuju Lansia Sejahtera di Kelurahan Heledulaa Selatan - jesica - Mulyadi; Serly - Daud (Universitas Negeri Gorontalo, 2026)
The elderly are the most vulnerable group to degenerative diseases due to the ageing process, which causes a decline in the body's physiological functions. Degenerative diseases such as hypertension, diabetes mellitus, and metabolic disorders are commonly found in the elderly and have an impact on their quality of life and increase their need for health services. Free health check-ups and medical treatment were conducted in South Heledulaa Subdistrict, targeting 29 elderly people, with the aim of early detection of risk factors for degenerative diseases and providing health education. The check-ups included measurements of blood pressure, blood glucose, cholesterol, and uric acid. The results showed that 62.06% of the elderly had degenerative diseases, consisting of 34.48% with hypertension and 27.58% with diabetes mellitus. Additionally, high uric acid levels were detected in 15 people, high cholesterol in 14 people, and high blood sugar in 10 people. These findings illustrate the high risk and burden of degenerative diseases in the elderly. Educational activities and routine check-ups have proven to be important in raising awareness, encouraging healthy lifestyles, and facilitating the continuous monitoring of the health conditions of the elderly.Keywords: elderly, degenerative diseases, health check-ups, early detection